Integration of Waiting Room ?Know Your Rights? Education into Medical Care of Immigrant Patients in a Federally Qualified Health Center: A Case Study (Mary Ann Liebert, 2022)
Background: Federally qualified health centers (FQHCs) are implementing innovative interventions to address heightened anxieties of immigrant patients amid changing immigration policies. Purpose: To describe the integration of ?Know Your Rights? legal rights education in clinic waiting rooms of an FQHC in Los Angeles, California. Methods: This is a qualitative study using key informant interviews, direct field observations, and document review. Results: Collaboration with community health workers and local immigrant-serving community-based and legal organizations was key to intervention design and implementation. Conclusion: Integrating legal education into medical care is one action health centers can take to support immigrant patients, address their complex realities, and optimize patients.